The Development and Standardization of a Competing Sentence Test in Kannada - R, Hemalatha (Journal of All India Institute of Speech and Hearing)
Jerger (1975), proposed the subtlety principle, which is as follows The more centrally the union is located, the more subtle is its manifestation. Hence to diagnose central auditory disorders (CAD) auditory tests need to be very sophisticated. The conventional audiometric test battery does not satisfy this criteria. Several authors have attempted to develop speech tests which may help in the diagnosis of CAD problems (Beasley and Freeman, 1977, Bocca, Calero and Cassinari, 1954; Costello, 1977; Jerger, Speaks and Trammel, 1968, Katz, 1978; Matzker, 1959). Their tests invariably use degraded speech material. Lynn and Gilroy (1977) have been particularly successful in demonstrating the clinical evaluation of central auditory tests in the diagnosis of CAD. Willeford and Billger (1978), found that children with learning disabilities show poor performance on central auditory tests. The following test battery was administered and it was seen that the children failed on at least one subject.